2015
DOI: 10.1080/15685551.2015.1070500
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles vs. nanofibers: a comparison of two drug delivery systems on assessing drug release performance in vitro

Abstract: In this study, the different encapsulation methods involving emulsification and coaxial electrospinning were both utilized to fabricate a series of core/sheath composite, nanoparticles (NPs) and Nanofibers (NFs) separately, for drug delivery on potential biological and therapeutic applications. Bovine serum albumin (BSA) was employed as an active pharmaceutical ingredient model for core; poly(L-lactic acid) (PLLA) and methoxy poly(ethyleneglycol)-Poly lactic acid (mPEG-PLA) were selected as the encapsulation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…A pertinent question is whether the drug carrier morphology matters in the context of tissue regeneration and which morphology is better, particles or fibers? To answer this question, FITC-tagged bovine serum albumin (BSA-FITC)-encapsulated nanoparticles and nanofibers of PLLA and m-PEG-PLLA were fabricated, respectively, and the release profiles indicated a burst release of BSA-FITC from the nanoparticles, while a slower sustained release was recorded over 10 days with nanofibers [31]. In another work, drug release and degradation profiles of electrospun poly( D,L -lactide) nanofibers could be modulated by varying the fiber diameter, thus suggesting nanofibers as alternative drug carriers compared to nanoparticles and thin films [32].…”
Section: Discussionmentioning
confidence: 99%
“…A pertinent question is whether the drug carrier morphology matters in the context of tissue regeneration and which morphology is better, particles or fibers? To answer this question, FITC-tagged bovine serum albumin (BSA-FITC)-encapsulated nanoparticles and nanofibers of PLLA and m-PEG-PLLA were fabricated, respectively, and the release profiles indicated a burst release of BSA-FITC from the nanoparticles, while a slower sustained release was recorded over 10 days with nanofibers [31]. In another work, drug release and degradation profiles of electrospun poly( D,L -lactide) nanofibers could be modulated by varying the fiber diameter, thus suggesting nanofibers as alternative drug carriers compared to nanoparticles and thin films [32].…”
Section: Discussionmentioning
confidence: 99%
“…The results may due to their different molecular structure/morphology-dependent cellular interactions and drug release; the spherical complex aggregates have comparably smaller size and larger surface area than the aggregates with other morphologies, which may endow them with their higher cellular uptake and drug release manners. Likewise, Zheng et al [ 65 ] reported that drug release behavior was determined by the matrix morphologies and the interactions between drug and matrix, and the methoxy poly(ethyleneglycol)-poly(lactic acid) (mPEG-PLA) nanofibrous vectors showed BSA release slower than that of their nanoparticle counterparts with corresponding kinetic t 1/2 (time for 50% drug release) of 175.5 h and 11.76 h, respectively. Alternatively, methotrexate (MTX) decorated MPEG-PLA nanobacillus (MPEG-PLA-MTX NB) prepared by Hou et al [ 35 ] were shown to enhance cell internalization, accumulation, and tumor inhibition superiorly to that of the MPEG-PLA-MTX spherical nanoparticles in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…39 Many investigators have evaluated nanofibers as a drug delivery device compared to nanoparticles. [39][40][41] For example, Shan et al reported that nanofibers of methoxy poly(ethylene glycol)poly lactic acid copolymer provide better zero-order release kinetics of drugs, while burst drug release was observed from nanoparticles. 40 For these reasons, drug-eluting nanofibers have received attention from many research groups for application in DES.…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41] For example, Shan et al reported that nanofibers of methoxy poly(ethylene glycol)poly lactic acid copolymer provide better zero-order release kinetics of drugs, while burst drug release was observed from nanoparticles. 40 For these reasons, drug-eluting nanofibers have received attention from many research groups for application in DES. 12,26,[36][37][38] Kim et al reported that a paclitaxel-eluting nanofiber-covered stent effectively inhibited colon cancer cells and extended stent patency.…”
Section: Discussionmentioning
confidence: 99%